A Literature Review on Gamification as an Interactive Approach in Mathematics Learning for Elementary School Students - Mursalin, M; Saputra, Eri; Ali, Muhammad (SAINTIS Publishing, 2024)
Students' interest and involvement in mathematics learning, particularly at the elementary school level, is often low due to the nature of the material that is considered difficult and less interesting. The gamification approach, which integrates elements of play into learning, emerges as a potential strategy to increase students' motivation and understanding of mathematical concepts. This study aims to analyze the effectiveness of gamification in increasing learning interest and understanding of mathematics in elementary school students. This literature review was carried out by collecting, filtering, and analyzing various relevant previous research, using keywords such as